2004
DOI: 10.1177/0273475303262350
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Marketing Education and Information Technology: Matching Needs or Needing a Better Match?

Abstract: The use of new information technology in marketing education has been widely, and often uncritically, accepted as both inevitable and beneficial with little in-depth analysis of this phenomenon, which is both a new mode of teaching (and learning) and a competency domain in its own right. This article examines both the potential advantages and dangers of information technology in the context of creating knowledge workers for the marketing industry. Research findings are presented to illustrate that students hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 42 publications
2
50
0
4
Order By: Relevance
“…The questionnaire was developed based on previous scales (e.g. Abrantes et al, 2007;Hunt et al, 2004). An online questionnaire was proposed to the students between February and April of 2013.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire was developed based on previous scales (e.g. Abrantes et al, 2007;Hunt et al, 2004). An online questionnaire was proposed to the students between February and April of 2013.…”
Section: Methodsmentioning
confidence: 99%
“…Potentially, students may withdraw several advantages of technologies use: first for their own skills development in using IT; also IT use offers new ways of mediated learning helping students to receive information more effectively, giving them more autonomy and freedom, and increasing their performance (Aleven&Koedinger, 2002;Hunt, Eagle & Kitchen, 2004).…”
Section: Learning Resourcesmentioning
confidence: 99%
“…No son muchos los trabajos realizados sobre innovación en los procesos de aprendizaje (Baena et al, 2008) y los pocos que han abordado este tema no pueden generalizarse a todo el sistema educativo ya que en la mayoría de los casos, fueron llevados a cabo con estudiantes de Universidades norteamericanas y británicas pertenecientes a titulaciones técnicas o de ciencias de la salud (Hunt, Eagle y Tchen, 2004;Meterissian, Liberman y McLeod, 2007, entre otros). Este artículo pretende contribuir a la literatura y subsanar esta limitación.…”
Section: -Discusión Y Conclusionesunclassified
“…En este sentido, algunos trabajos demuestran lo difícil que puede resultar adquirir determinadas competencias, tales como el liderazgo, gestión de personas, distribución de tareas (Adrian y Palmer, 1999), o trabajo en equipo (Wright, Bitner y Zeithaml, 1994), si el alumno se limita a seguir un aprendizaje meramente pasivo. Sin embargo, es relativamente escaso el número de estudios que han analizado este aspecto y la mayoría de los que lo han hecho se han centrado en el sistema educativo anglosajón (Elliot y Shin, 2002;Hunt, Eagle y Tchen, 2004;Meterissian, Liberman y McLeod, 2007;Christensen, Horn y Johnson, 2008), lo que dificulta su extrapolación al entorno del EEES. El objetivo del presente trabajo es cubrir este vacío.…”
Section: -Introducciónunclassified
“…Alavi (1994) conducted a review of literature and research on cognitive learning theory and found that no single or unified learning theory exists, however she identified three attributes that assist in creating an environment where effective learning takes place and they are: "active learning and constructing knowledge", "cooperation and teamwork in learning" and "learning via problem solving". The integration of information technology into the learning process has the potential to enhance the effectiveness of learning (Clarke et al, 2001;Hunt et al, 2004), although as some authors (Pitt, 2007) have pointed out, information technology cannot be viewed as a panacea to all educational and pedagogical problems.…”
Section: Collaborative and Constructive Learningmentioning
confidence: 99%